2020
DOI: 10.4103/ijpvm.ijpvm_379_19
|View full text |Cite
|
Sign up to set email alerts
|

Adherence of general practitioners to the national hypertension guideline, Isfahan, Iran

Abstract: Background: High systolic blood pressure is the leading risk factor for global mortality. Applying effective strategies to control hypertension is a rising concern. Guidelines are approved to be effective in the management of patients with cost-effective interventions. The aim of this study is to evaluate the adherence of family physicians working in Isfahan health centers to the national hypertension guideline, in 2019. Methods: Using a cross-sectional study, the pract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…This, in turn, leads to an increase in workload and resistance to change among doctors, ultimately resulting in noncompliance to CPGs. The studies also highlighted a lack of motivation and inadequate relationships among staff as additional barriers ( 32 , 34 , 38 – 41 ). Dishonesty within the system and a lack of commitment hinder teamwork and the implementation of guidelines.…”
Section: Resultsmentioning
confidence: 99%
“…This, in turn, leads to an increase in workload and resistance to change among doctors, ultimately resulting in noncompliance to CPGs. The studies also highlighted a lack of motivation and inadequate relationships among staff as additional barriers ( 32 , 34 , 38 – 41 ). Dishonesty within the system and a lack of commitment hinder teamwork and the implementation of guidelines.…”
Section: Resultsmentioning
confidence: 99%
“…Physician knowledge and adherence to guidelines pose additional challenges. A Study in Iran reported that only 31.8% of physicians were familiar with clinical guidelines 40 , and family physicians adhered to only one-third of the recommendations in the national hypertension guideline 19 . Among cardiologists at a teaching hospital in Iran, only 60% exhibited high adherence to the ACC/AHA guidelines in managing cardiovascular disease risk factors 41 .…”
Section: Discussionmentioning
confidence: 99%
“…This debate underscores the need for country-speci c investigations to estimate hypertension burdens based on different guidelines In Iran, similar to many countries, JNC7 remains the predominant guideline for de ning and treating hypertension. Despite guidelines like IraPen, which is developed based on the World Health Organization (WHO) Package of essential noncommunicable disease (PEN) interventions for primary health care in lowresource settings (WHO PEN) 17,18 , and the national family physician HTN guideline 19 aligning with JNC7 thresholds, the recent slow adoption of the ACC/AHA guideline in Iran suggests a changing trend 20 . Hence, exploring the potential impact of different guidelines on hypertension stage prevalence in Iran is crucial.…”
Section: Introductionmentioning
confidence: 99%
“…It is shown that high LDL-C contributed to 16.1% of deaths and 7.8% of DALYs caused by non-communicable diseases (NCDs) in the Iranian population in 2019 4 . The high consumption of dietary fats, obesity, physical inactivity, non-adherence to treatment guidelines by patients and physicians, as well as the increasing consumption of carbohydrate-rich foods could predispose the Iranian population to dyslipidemia 5 – 9 . Meanwhile, the widespread prescribing of statins by general practitioners, restrictions on trans fats in edible oils, and increased public awareness of the risk factor are policies and trends that may decrease dyslipidemia prevalence in Iran 3 , 10 .…”
Section: Introductionmentioning
confidence: 99%